Analysis of the Correlations between the Characteristics of miRNAs Expression in Serum or Plasma and Hyperactivity of Liver-YANG Syndrome of Hypertension - Changgeng FU (康复学报)
This review documented a possibility of the correlations between the miRNAs expression characteristics in serum or plasma and hyperactivity of liver-YANG syndrome of hypertension (HLYS).based on the discovery of miRNAs and its roles in the occurrence and development of hypertension, combined traditional Chinese medicine syndrome of HLYS. This article would proride the basis for the scientific connotation and early prevention and treatment for HLYS.